March 1968—the Thirteen Thousand Forgotten People of Poland. Some Linguistic Reflections on the Support of Testimonies - Pirogowska, Ewa (Sensus Historiae, 2025)
The article discusses linguistic reflections on the forced migration of Jews from Poland in 1968, following an anti-Semitic campaign. It highlights how the Polish society has evolved since then with increased awareness and recognition of Jewish heritage, despite ongoing anti-Semitic sentiments. The study analyses oral testimonies from Jewish witnesses of the 1968 events collected by the Teatr NN—Brama Grodzka cultural centre in Lublin. These testimonies reveal personal experiences and perceptions of anti-Semitism. The article also explores the challenges of translating such testimonies into French as the emotional connotations are often lost. The text concludes by emphasizing the importance of discourse analysis in understanding historical events like the 1968 Polish anti-Semitic campaign and its ongoing impact on Jewish identity and anti-racist efforts.